ANALISIS PENGARUH PERUBAHAN PERATURAN PERPAJAKAN PADA SEKTOR USAHA JASA KONSTRUKSI DI INDONESIA - M Khoiru Rusydi (Universitas Brawijaya, 2010)
Construction service business sector is one of the sectors that experience a rapid growth after economic crisis in 1998. In 2002, the value of capitalization industry reached up to Rp.110,052 billion and kept on increasing up to Rp 173,44 billion in 2005. There are 96.000 registered taxpayers both personal and corporate. However, the increasing capitalization is not comparable to the increasing tax collection (PPh article 23). For example in 2005 when the value of capitalization was Rp. 173,44 billion, the contribution of tax for this sector reached only Rp 1,7 trilliun or 1%. Such discrepancy urges the government to establish regulation namely Peraturan Pemerintah Republik Indonesia Nomor 51 Tahun 2008 on Tax of Construction Business Service. This regulation is an amendment of Peraturan Perpajakan Nomor 140 Tahun 2000. There is a change in project gross profit tariff and its final treatment based on its classification. Less than a year later, debates surrounding this regulation gave way to a new regulation Nomor 40, 2009. This article is aimed to analyze the discrepancy caused by the three regulations. There is a significant change of 1.4% for planning and controlling service. There is 2.35% change of tariff for executor service provider.